Aplikasi Pencarian Pendonor Darah Untuk Pasien Menggunakan Metode Extreme Programming Berbasis Mobile - Fajrian Nur; Muchamad Zainul Rohman; Farindika Metandi (CV MEDAN TEKNO SOLUSI, 2024)
This research aims to develop a mobile application for blood stock information, blood requests, and donor searches using Extreme Programming (XP) methodology at the Indonesian Red Cross (PMI) in Balikpapan City, East Kalimantan. The main issue addressed is the process of finding blood donors for patients. Using the XP approach, the application is designed to provide information on the availability of blood stocks according to the blood type and specific needs of the patients. The research method includes Planning, Design, Coding, Testing phases. Data collection techniques involve observation, interviews, and literature studies. The application is developed using the Dart programming language and Firebase as the database. It is hoped that the developed application will provide significant benefits to patients and relevant parties at PMI Balikpapan City, as well as contribute to the advancement of information technology in the healthcare field